1000 statistics on investigations menopausal women - Arenas, Normando (2015)
Biological phenomena and especially those in the medical field, multiple causes and variables, given its atypical, their measures can only be determined based on the statistical method. N. Louis argues that statistics in medicine should be the inseparable instrument of the inductive method, to play a significant role in the production chance of such phenomena, the advantages arising from the application of the notion of probability to the medical facts.